A New Numerical Method for Calculation of Micro- Stress on Unidirectionally Reinforced Plates with Circular Hole In Case of Extension to a Principal Direction - Darya zadeh, S.; Lvov, G. I.; Daryazadeh, P. (ORIC Publications, 2014)
The aim of the present study was to compute the stress concentration in reinforced composite plate with circular hole with respect to the volume ratio of the component materials in composite. The contour of the circular hole and its dependency on the structure of plates were calculated in order to study the behaviors of macro and micro-stresses. The boundary conditions at a large distance from the hole are pressure, uniformly distributed on the plate. Also this problem is analyzed with the finite element method by package ANSYS. The results demonstrated the macro and micro stress and behavior of the orthotropic plate with a circular hole calculated for two different structures.
Keywords: boundary conditions; composite plate; numerical method; unidirectional reinforced; stress concentration